Google Translate on English Writing Evidence of EFL University Students - Siti Masruroh,; Daviq Rizal, (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
This study investigates the Google Translate English writing evidence of English department and less-proficient non-English department students and students' perceptions of translating activities using Google Translate. Through the quantitative research, the researcher distributed a survey in the form of a Google form to 100 students majoring in English and non-English departments. A questionnaire was used to collect the opinions of the students on the activity. The results showed that Google Translates text exhibits authoring performance that is noticeably better and provides more enriched content, employing a vocabulary more sophisticated and grammatical errors. Students use Google Translate because the tool shows better L2 performance in writing languages and tends to be instantaneous. The implications of this research are what students' perceptions of Google Translate are, and whether Google Translate can improve students' writing skills.